Professor A.G. Knorre: the life and scientific-pedagogical activity (on the 100th anniversary of his birth) - M. V. Mnihovich; V. L. Zagrebin (Морфологія, 2014)
In 2014, 100 years have passed since the birth of one of the largest biologists of our country, a learned histologist and embryologist, corresponding member of the Academy of Medical Sciences of the USSR, Professor Alexei Georgievich Knorre.